The laws regulating co-operative banks and the contribution to economic growth and poverty alleviation in South Africa - Gundani, Simbarashe Roy (My University, 2017)
The world, more especially countries in Africa are battling with the effects of poverty, unemployment and destitution. South Africa is one African country that succumbed to racial inequality brought about by apartheid wherein black people were denied participation into any form of income generating endeavours that would ensure their sustenance. The South African Government after attaining independence in 1994 put in place policies meant to emancipate and empower the Historically Disadvantaged People (HDP). In line with that approach, the government deemed it fit to empower the South African populace through Co-operatives. This study analyses and critiques the Co-operative Banks Act, 40 of 2007 as the focal instrument regulating financial co-operatives in South Africa and its contribution towards economic growth and poverty reduction. The study further exposes some of the imminent challenges experienced in the field of financial co-operatives as far as registration of such cooperatives is concerned. The Act since its inception has only managed to have only two co-operative banks established and the rest of the Co-operative Financial Institutions (CFI’s) are not registered and are operating under an exemption notice. Therefore, this study brings to light some of the challenges leading to the failure to become co-operative banks, and also delves into the act itself to assess whether its provisions are the reason for this ultimate failure to register financial co-operatives. The challenges experienced by financial co-operatives in South Africa would be addressed by drawing lessons from countries such as Kenya and Canada which have managed to establish a strong and vibrant co-operative industry so as to suggest ways in which they may also improve and graduate to become successful Co-operative Banks.
Thesis (LLM.) -- University of Limpopo, 2017.
Keywords: Co-operative banks; Economic growth; Poverty alleviation; Banks and banking, Cooperatives -- Law and legislation -- South Africa; Banking laws -- South Africa; Economic development -- South Afica; Poverty -- South Africa